2023
DOI: 10.1111/jnc.15988
|View full text |Cite
|
Sign up to set email alerts
|

Associations of liver dysfunction with incident dementia, cognition, and brain structure: A prospective cohort study of 431 699 adults

Pei‐Yang Gao,
Ya‐Nan Ou,
Hui‐Fu Wang
et al.

Abstract: The relationship between liver dysfunction and dementia has been researched extensively but remains poorly understood. In this study, we investigate the longitudinal and cross‐sectional associations between liver function and liver diseases and risk of incident dementia, impaired cognition, and brain structure abnormalities using Cox proportion hazard model and linear regression model. 431 699 participants with a mean of 8.65 (standard deviation [SD] 2.61) years of follow‐up were included from the UK Biobank; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…However, no study so far demonstrated whether D3 modi es its function in the brain secondary to different diseases, as Alzheimer, or the metabolic dysfunction associated steatotic liver disease (MASLD). Remarkably, as in Alzheimer disease (AD), liver dysfunction is accompanied by cognitive loss (Gao et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…However, no study so far demonstrated whether D3 modi es its function in the brain secondary to different diseases, as Alzheimer, or the metabolic dysfunction associated steatotic liver disease (MASLD). Remarkably, as in Alzheimer disease (AD), liver dysfunction is accompanied by cognitive loss (Gao et al, 2024).…”
Section: Introductionmentioning
confidence: 99%